Eksplorasi Ketersedian Pangan Rumah Tangga pada Balita SAD Beresiko Stunting di Kabupaten Muaro Jambi - Yurizal Yurizal; Yesi Nurmawi (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
The prevalence of stunting among the Suku Anak Dalam (SAD) in Nyogan Village, Muaro Jambi, reached 42.2%, far exceeding the district average. Ecosystem changes due to forest conversion forced the SAD to shift from nomadic to settled lifestyles, impacting household food availability. This study explored food availability in families of SAD toddlers at risk of stunting. This qualitative study, using an ethnographic design, was conducted from May–December 2023. Data were collected from 20 informants through in-depth interviews, focus group discussions (FGDs), observation, and anthropometry. Data analysis was conducted thematically using the Onion Diagram and Food Consumption Score (FCS) approaches. The stunted SAD toddlers came from households with "threshold" food availability (FCS score 35). Although cereal consumption was met, intake of animal protein, vegetables, and fruit was very low. Food availability was highly dependent on river fish caught, which were sold to buy market groceries, but low purchasing power limited access to a balanced, nutritious diet. Low household food availability is a major determinant of stunting in SAD. Nutrition education regarding affordable local foods and support for more stable food access for this marginalized community are needed.